Aerogel thermal insulation material with magnetic function and preparation method thereof

By doping rare earth elements into airgel materials and optimizing the preparation process, the deficiencies in the thermal insulation performance and magnetic function balance of existing magnetic airgel materials are solved, achieving dual performance improvement of the material and simplification of the process, and broadening the scope of Its application range in many fields.

CN119349980APending Publication Date: 2025-01-24TIANMUSHAN LABORATORY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411240867.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing magnetic aerogel materials have shortcomings in the balance between thermal insulation performance and magnetic functions. The introduction of magnetic nanoparticles will destroy the porous structure of aerogel materials, resulting in a decrease in thermal insulation performance. At the same time, the preparation process is complex and the production cost is high. , limits the large-scale application of materials in practical applications.

Method used

By rationally designing the doping strategy of rare earth elements and optimizing the preparation process of nanowire aerogels, hydrothermal reaction and supercritical drying steps were used to prepare titanium dioxide nanowire aerogel materials doped with rare earth elements.

Benefits of technology

The dual improvement of magnetic and thermal insulation properties is achieved. The material has excellent thermal insulation effect and significant magnetic function, and has better high-temperature thermal insulation properties and mechanical strength. The preparation process is simple and easy for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349980A_ABST
    Figure CN119349980A_ABST
Patent Text Reader

Abstract

The invention relates to an aerogel thermal insulation material with a magnetic function and a preparation method thereof, and the method comprises the following steps: mixing titanium oxide nano powder, an alkaline solution and precursor lanthanum nitrate (La (NO3) 3.6 H2O) of rare earth elements in deionized water, and mechanically stirring to obtain a mixed solution; placing the mixed solution in a closed container for hydrothermal reaction to obtain a semi-solid gel block; dipping the gel block in an acid solution for pickling, and washing the pickled gel block with water; the washed gel block is subjected to a solvent replacement process and a supercritical drying step, and nanowire aerogel is prepared; and finally, carrying out heat treatment on the nanowire aerogel. According to the preparation method, the rare earth element doped titanium dioxide nanowire aerogel thermal insulation material with a magnetic function can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerogel preparation, and in particular to an aerogel thermal insulation material with magnetic function and a preparation method thereof. Background Art

[0002] Aerogel materials have been widely used in the fields of thermal insulation, catalysis, sensing and environmental management due to their unique nanoporous structure, ultra-low density and excellent thermal insulation performance. The thermal insulation performance of traditional aerogel materials is very superior, and its room temperature thermal conductivity can be as low as 0.01W / m·K, making it one of the solid materials with the lowest thermal conductivity known. However, traditional aerogel materials, such as silica aerogel, usually do not have magnetic functions, which limits their application in some special fields that require both thermal insulation and magnetic functions. For example, in the fields of magnetic fluid seals, stealth materials, satellite components and sensor devices, the material must not only have good magnetic response, but also be able to effectively isolate heat conduction.

[0003] Chinese patent application CN202311490484.8 discloses a magnetic aerogel and its preparation method and application, which uses citric acid monohydrate to crosslink ferroferric oxide nanoparticles with sodium carboxymethyl cellulose to obtain a magnetic cellulose aerogel. Although the aerogel is magnetic by doping ferroferric oxide nanoparticles, it is mainly used in the field of dye adsorption. Cellulose aerogel does not have an advantage in high-temperature applications, so the high-temperature thermal insulation performance of the aerogel material may not be very good.

[0004] Chinese patent application CN202010381704.3 discloses a Fe3C-SiO2 magnetic aerogel and a preparation method thereof, wherein the composite form of the aerogel is that Fe3C particles are dispersed in a SiO2 matrix. Although this composite aerogel has good application prospects in the fields of microwave absorption and adsorption recovery, the presence of Fe3C may increase thermal conductivity and interfere with the continuous porous structure of the SiO2 aerogel, and the application of the Fe3C-SiO2 composite aerogel in the field of thermal insulation may be limited.

[0005] It can be seen from the above patented technology that although the existing magnetic aerogel materials have made some progress in magnetic function, they still have obvious deficiencies in the balance between thermal insulation performance and magnetic function. The introduction of magnetic nanoparticles often destroys the porous structure of aerogel materials, resulting in a decrease in their thermal insulation performance. In addition, the current preparation process is relatively complicated and the production cost is high, which limits the large-scale application of these materials in practice.

[0006] In view of the above problems, the present invention proposes an aerogel thermal insulation material with magnetic function and a preparation method thereof. By rationally designing the doping strategy of rare earth elements and optimizing the preparation process of nanowire aerogel, the present invention successfully achieves a dual improvement in magnetic and thermal insulation performance. The prepared aerogel material not only has excellent thermal insulation effect, but also has significant magnetic function. Compared with the prior art, the material of the present invention has better high-temperature thermal insulation performance and mechanical strength, and the preparation process is simpler and easy to achieve large-scale production, which significantly broadens its application range in aerospace, magnetic separation, absorbing materials and magnetron catalysis. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides an aerogel thermal insulation material with magnetic function and a preparation method thereof.

[0008] In a first aspect, the present invention provides a method for efficiently preparing a high temperature radiation resistant aerogel thermal insulation material, the method comprising the following steps:

[0009] (1) mixing titanium oxide nanopowder, alkaline solution and rare earth element precursor with deionized water, and obtaining a mixed solution by stirring and ultrasonic treatment;

[0010] (2) placing the mixed solution in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction to obtain a semi-solid wet gel block;

[0011] (3) soaking the wet gel block in an acidic solution for acid washing;

[0012] (4) washing the gel block after acid washing with water;

[0013] (5) placing the washed gel block in an ethanol solution for solvent replacement;

[0014] (6) subjecting the gel block after solvent replacement to a supercritical drying step and a heat treatment step to obtain a rare earth element-doped titanium dioxide nanowire aerogel material.

[0015] Furthermore, in step (1), the alkaline solution is potassium hydroxide and / or sodium hydroxide solution, the concentration is 8-12 mol / L, the precursor of the rare earth element is lanthanum nitrate (La(NO3)3·6H2O), and the mass fraction of titanium oxide nanopowder in the mixed solution is 1%-15%.

[0016] The mass fraction of the rare earth element precursor in the mixed solution is 0.5%-8%.

[0017] Furthermore, in step (2), the mixed liquid is placed in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction, which is to place the mixed liquid in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction at 150-300° C. for 12-48 hours to obtain a semi-solid gel block.

[0018] Furthermore, in step (3), the pH of the acidic solution is 1 to 5, the acidic solution is one or more of hydrochloric acid, sulfuric acid and nitric acid solution, the amount of the acidic solution is 1 to 10 times the volume of the gel block, the pickling time is 12 to 72 hours, and step (3) is repeated 1 to 3 times.

[0019] Furthermore, in step (4), the amount of water used is 5-20 times the volume of the gel block, the water washing time is 1-6 hours, and step (4) is repeated 2-5 times.

[0020] Furthermore, in step (5), the amount of ethanol used is 5-10 times the volume of the gel block, the replacement time is 24-72 hours, and step (5) is repeated 1-3 times.

[0021] Furthermore, in step (6), the temperature of the supercritical drying is 20-60° C., and the pressure is 10-16 MPa. The treatment atmosphere of the heat treatment is an inert atmosphere, the treatment temperature is 500-800° C., and the treatment time is 0.5-3 h.

[0022] In a second aspect, the present invention provides an aerogel thermal insulation material with magnetic function, which is prepared by the preparation method described in the first aspect of the present invention.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] (1) By doping titanium dioxide nanowires with rare earth elements, the thermal stability of the material can be improved, allowing it to maintain good thermal insulation properties at higher temperatures and be suitable for a wider range of industrial applications.

[0025] (2) The addition of rare earth elements helps to improve the mechanical strength of aerogels, making them more durable and reducing material loss caused by mechanical wear or breakage during application.

[0026] (3) The introduction of magnetic functions into aerogels can be used in specific industrial fields that require magnetic thermal insulation materials, such as providing thermal insulation protection in magnetically driven environments.

[0027] (4) Rare earth element-doped titanium dioxide nanowire aerogels exhibit better chemical and physical stability under various environmental conditions (such as high humidity and extreme temperature) and have better environmental adaptability.

[0028] (5) Using hydrothermal reaction and supercritical drying steps, this method can efficiently and uniformly synthesize nanowire aerogels with consistent properties, improving production efficiency and reducing costs.

[0029] (6) Due to the unique properties of rare earth elements, the thermal conductivity of this material can be further reduced, thereby providing better thermal insulation effect.

[0030] (7) By adjusting the type and doping amount of rare earth elements, the magnetic properties of aerogels can be precisely controlled to achieve customizable magnetic properties that meet the magnetic and thermal insulation properties of different applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a preparation flow chart of the present invention.

[0032] Figure 2 This is a physical picture of the aerogel prepared in Example 1.

[0033] Figure 3 is a SEM image of the aerogel prepared in Example 1. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] In a first aspect, the present invention provides an aerogel thermal insulation material with magnetic function and a preparation method thereof, the method comprising the following steps:

[0036] (1) mixing titanium oxide nanopowder, alkaline solution and rare earth element precursor with deionized water, and obtaining a mixed solution by stirring and ultrasonic treatment;

[0037] (2) placing the mixed solution in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction to obtain a semi-solid wet gel block;

[0038] (3) soaking the wet gel block in an acidic solution for acid washing;

[0039] (4) washing the gel block after acid washing with water;

[0040] (5) placing the washed gel block in an ethanol solution for solvent replacement;

[0041] (6) subjecting the gel block after solvent replacement to a supercritical drying step and a heat treatment step to obtain a rare earth element-doped titanium dioxide nanowire aerogel material.

[0042] Furthermore, in step (1), the alkaline solution is potassium hydroxide and / or sodium hydroxide solution with a concentration of 8 to 12 mol / L, the precursor of the rare earth element is lanthanum nitrate (La(NO3)3·6H2O), the mass fraction of titanium oxide nanopowder in the mixed solution is 1%-15%, and the mass fraction of the precursor of the rare earth element in the mixed solution is 0.5%-8%.

[0043] Furthermore, in step (2), the mixed liquid is placed in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction, which is to place the mixed liquid in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction at 150-300° C. for 12-48 hours to obtain a semi-solid gel block.

[0044] Furthermore, in step (3), the pH of the acidic solution is 1 to 5, the acidic solution is one or more of hydrochloric acid, sulfuric acid and nitric acid solution, the amount of the acidic solution is 1 to 10 times the volume of the gel block, the pickling time is 12 to 72 hours, and step (3) is repeated 1 to 3 times.

[0045] Furthermore, in step (4), the amount of water used is 5-20 times the volume of the gel block, the water washing time is 1-6 hours, and step (4) is repeated 2-5 times.

[0046] Furthermore, in step (5), the amount of ethanol used is 5-10 times the volume of the gel block, the replacement time is 24-72 hours, and step (5) is repeated 1-3 times.

[0047] Furthermore, in step (6), the temperature of the supercritical drying is 20-60° C., and the pressure is 10-16 MPa. The treatment atmosphere of the heat treatment is an inert atmosphere, the treatment temperature is 500-800° C., and the treatment time is 0.5-3 h.

[0048] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.

[0049] Example 1

[0050] (1) 2 g of titanium oxide nanopowder was dissolved in 97 g of 10 M potassium hydroxide solution, and then 1 g of lanthanum nitrate (La(NO3)3·6H2O) was added, the mass fraction of titanium oxide nanopowder in the obtained mixed solution was 2%, and the mass fraction of lanthanum nitrate (La(NO3)3·6H2O) in the obtained mixed solution was 1%. After mixing, the mixture was stirred in a homogenizer for 120 min.

[0051] (2) The mixed solution is placed in a reactor lined with para-polyphenol (PPL) material, and placed in an oven at 240° C. for 24 hours. After the reaction is completed, a semi-solid gel block is obtained.

[0052] (3) The wet gel block is immersed in an acid solution (pH 1) for pickling. The amount of acid solution used is 5 times the volume of the gel block. The liquid level covers the gel block. The pickling time is 48 hours and repeated twice.

[0053] (4) The acid-washed gel blocks were washed with water, the amount of water used was 10 times the volume of the gel blocks, the washing time was 2 h, and repeated 3 times.

[0054] (5) The washed gel blocks were placed in an ethanol solution for solvent replacement. The amount of ethanol used was 5 times the volume of the gel blocks. The liquid level covered the gel blocks. The replacement time was 72 hours and repeated 3 times.

[0055] (6) The gel block after solvent replacement is subjected to a supercritical drying step and a heat treatment step, wherein the supercritical drying temperature is 50° C. and the pressure is 14 MPa. The heat treatment atmosphere is an inert atmosphere, the treatment temperature is 600° C., and the treatment time is 2 h, thereby obtaining a rare earth element-doped titanium dioxide nanowire aerogel material.

[0056] (7) The prepared aerogel has a heat resistance temperature of 700°C, a room temperature thermal conductivity of 0.025 W / m·K, and a density of 0.035 g / cm 3 , saturation magnetization 6.14emu / g.

[0057] Example 2

[0058] Example 2 is substantially the same as Example 1, except that the amount of titanium oxide nanopowder in step 1 is 10 g.

[0059] The thermal insulation performance of the aerogel material in Example 2 was tested, and it was found that the surface of the aerogel material did not change color and did not fall off when gently touched. Other performance indicators are shown in Table 1.

[0060] Comparative Example 1

[0061] Comparative Example 1 is substantially the same as Example 1, except that lanthanum nitrate (La(NO3)3·6H2O) is not added during the preparation of the mixed solution in step 1.

[0062] The aerogel material prepared in Comparative Example 1 was tested for its saturation magnetization performance, and it was found that the saturation magnetization was 0. Other performance indicators are shown in Table 1.

[0063] Comparative Example 2

[0064] Comparative Example 2 is substantially the same as Example 1, except that during the preparation of the mixed solution in step 1, the mass fraction of the added lanthanum nitrate (La(NO3)3·6H2O) in the mixed solution is 10%.

[0065] The strength of the aerogel material prepared in Comparative Example 2 is relatively weak and no complete block is formed. Other performance indicators are shown in Table 1.

[0066] Comparative Example 3

[0067] Comparative Example 3 is substantially the same as Example 1, except that in the preparation of the mixed solution in step 1, the concentration of the potassium hydroxide solution is 6 mol / L.

[0068] The aerogel material prepared in Comparative Example 3 exhibits lower mechanical strength, and other performance indicators are shown in Table 1.

[0069] Comparative Example 4

[0070] Comparative Example 4 is substantially the same as Example 1, except that in the mixed solution preparation process of step 1, the concentration of the potassium hydroxide solution is 15 mol / L.

[0071] The mechanical properties of the aerogel material prepared in Comparative Example 4 are poor and there is a powdering phenomenon. Other performance indicators are shown in Table 1.

[0072] Comparative Example 5

[0073] Comparative Example 5 is substantially the same as Example 1, except that the hydrothermal reaction temperature in step 2 is 120°C.

[0074] The strength of the aerogel material prepared in Comparative Example 5 is weak, loose and brittle. Other performance indicators are shown in Table 1

[0075] Comparative Example 6

[0076] Comparative Example 6 is substantially the same as Example 1, except that the hydrothermal reaction time in step 2 is 9 h.

[0077] The aerogel material prepared in Comparative Example 6 exhibits poor mechanical properties and is easily broken. Other performance indicators are shown in Table 1.

[0078] Comparative Example 7

[0079] Comparative Example 7 is substantially the same as Example 1, except that the pickling in step 3 is not performed.

[0080] The aerogel material prepared in Comparative Example 7 cannot maintain structural integrity after heat treatment. Other performance indicators are shown in Table 1.

[0081] Comparative Example 8

[0082] Comparative Example 8 is substantially the same as Example 1, except that the supercritical drying process in step 6 is not performed, and atmospheric pressure drying is performed instead.

[0083] The aerogel material prepared in Comparative Example 8 has high density, large shrinkage, and a smooth surface. Other performance indicators are shown in Table 1.

[0084] Comparative Example 9

[0085] Comparative Example 9 is substantially the same as Example 1, except that the heat treatment process in step 6 is not performed.

[0086] The aerogel material prepared in Comparative Example 9 was tested for its heat resistance, and it was found that the heat resistance temperature was 200° C. Other performance indicators are shown in Table 1.

[0087] Comparative Example 10

[0088] Comparative Example 10 is substantially the same as Example 1, except that the treatment atmosphere of the heat treatment process in step 6 is an air atmosphere.

[0089] The aerogel material prepared in Comparative Example 10 was tested for its saturation magnetization performance, and it was found that the saturation magnetization was 0.21emu / g. Other performance indicators are shown in Table 1.

[0090] Comparative Example 11

[0091] Comparative Example 11 is substantially the same as Example 1, except that during the preparation of the mixed solution in step 1, the mass fraction of the added titanium oxide nanopowder in the mixed solution is 0.5%.

[0092] The aerogel material prepared in Comparative Example 11 cannot form a semi-solid gel block after the hydrothermal reaction.

[0093] Table 1: Performance indicators of the radiation-resistant aerogel materials prepared in Examples 1 to 2 and the high-temperature resistant aerogel materials in Comparative Examples 1 to 11.

[0094]

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An aerogel thermal insulation material with magnetic function and a preparation method thereof, characterized in that: The method comprises the following steps: (1) Mix titanium oxide nanopowder, alkaline solution and rare earth element precursor with deionized water, A mixed solution is obtained by stirring and ultrasonic treatment; (2) placing the mixed solution in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction to obtain a semi-solid wet gel block; (3) soaking the wet gel block in an acidic solution for acid washing; (4) washing the gel block after acid washing with water; (5) placing the washed gel block in an ethanol solution for solvent replacement; (6) subjecting the gel block after solvent replacement to a supercritical drying step and a heat treatment step to obtain a rare earth element-doped titanium dioxide nanowire aerogel material.

2. The preparation method according to claim 1, wherein in step (1), the alkaline solution is potassium hydroxide and / or sodium hydroxide solution with a concentration of 8 to 12 mol / L, the precursor of the rare earth element is lanthanum nitrate (La(NO3)3·6H2O), the mass fraction of titanium oxide nanopowder in the mixed solution is 1%-15%, and the mass fraction of the precursor of the rare earth element in the mixed solution is 0.5%-8%.

3. The preparation method according to claim 1, in step (2), the mixing liquid is placed in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction, which is placing the mixing liquid in a reactor lined with para-polyphenol (PPL) material for hydrothermal reaction at 150-300° C. for 12-48 hours to obtain a semi-solid gel block.

4. The preparation method according to claim 1, in step (3), the pH of the acidic solution is 1 to 5, the acidic solution is one or more of hydrochloric acid, sulfuric acid and nitric acid solution, the amount of the acidic solution is 1 to 10 times the volume of the gel block, the pickling time is 12 to 72 hours, and step (3) is repeated 1 to 3 times.

5. The preparation method according to claim 1, wherein in step (4), the amount of water used is 5-20 times the volume of the gel block, the water washing time is 1-6 hours, and step (4) is repeated 2-5 times.

6. The preparation method according to claim 1, wherein in step (5), the amount of ethanol used is 5-10 times the volume of the gel block, the replacement time is 24-72 hours, and step (5) is repeated 1-3 times.

7. The preparation method according to claim 1, wherein in step (6), the temperature of the supercritical drying is 20-60°C and the pressure is 10-16 MPa. The treatment atmosphere of the heat treatment is an inert atmosphere, the treatment temperature is 500-800°C, and the treatment time is 0.5-3 hours.

8. An aerogel thermal insulation material with magnetic function, which is prepared by the preparation method according to any one of claims 1 to 7, wherein the aerogel has a heat resistance temperature of 500-800°C, a room temperature thermal conductivity of 0.024-0.048 W / m·K, and a density of 0.02-0.2 g / cm 3 , saturation magnetization 1-10emu / g.

Citation Information

Patent Citations

  • Fe3C-SiO2 magnetic aerogel and preparation method thereof

    CN111530387A

  • Magnetic aerogel as well as preparation method and application thereof

    CN117398974A